Прогнозирование валютного риска в дилинговых информационных системах - Фёдоров, Е. Г.; Шамша, Б. В. (My University, 2007)
Проведено оцінку ефективності моделей прогнозування валютного ризику в дилінгових інформаційних системах. Розглянуто моделі прогнозування стандартногоотклоненія прибутковості фінансового активу. The effectiveness of models of currency risk forecasting in dealing information systems was estimated. The models of forecasting the standard deviation of financial asset profitability are considered.
Keywords: валютный риск; дилинговая система